Analysis of Inflationary Burden Impact on The Consumption of Iraqi Households - Raed Salahddin, Tiba *; Siham Daoud, Samir (Journal of Economics and Administrative Sciences, 2024)
The research focused on examining the connection between the inflationary burden and the consumption patterns of Iraqi families. Inflation significantly impacts consumption, and Iraq is grappling with rising prices, leading to a crisis in the cost of living due to increased prices for essential goods and reduced government subsidies. The study aimed to provide insights into the inflationary burden phenomenon, highlight the primary channels affecting Iraqi families, and explore short and long-term consequences. It also aimed to identify the variables and causes contributing to the wage-price gap. Ultimately, the research sought to address the issue of the inflationary burden in the Iraqi economy, which has adversely affected the standard of living for families, resulting in reduced consumption and a diminished real value of money. The goal was to propose solutions to enhance living standards and manage price stability.Key findings :Recent years have seen a sharp increase in consumer spending as a percentage of total income, reaching 70%. This reflects the high prices of essential goods and services.The Iraqi economy has faced various crises, including war, the COVID-19 pandemic, exchange rate fluctuations, and global conflicts, leading to economic decline and worsened family conditions.Recommendations :Promote consumer spending awareness among Iraqi families through visual and audio advertising, encouraging responsible consumption and savings for future crises.Protect local products by imposing customs taxes on imports, except for essential items.Ensure coordination between fiscal and monetary policies to maintain price stability and boost consumer goods production, granting the central bank independence for policy development.